ENHANCING THE TALENT OF USM ACADEMICS AND STUDENTS THROUGH KTP - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 5 May 2015 Universiti Sains Malaysia (USM) will continue to enhance the talent of its academics and students through Knowledge Transfer Programmes (KTP) by encouraging them and members of USM community to deposit their novel ideas directly to BankIDEA@USM which (mailto:BankIDEA@USM which) can be accessed without any borders.